The Effect of Fibrinogen Degradation Products on Plasmin Activity - Myśliwiec, M; Arnesen, H; Godal, H. C (Thrombosis and Haemostasis, 1973)
Purified fibrinogen degradation products Y, D or E were not found to exert antiplasmin activity as measured by the clot lysis time.Spontaneous inactivation of plasmin was observed during incubation at 37° C. This inactivation was partly prevented by the presence of fibrinogen degradation products, as well as by other proteins.